Recurrence and 5-year survival rate in patients with borderline ovarian tumors and related factors in Kurdistan - Seyedeh Reyhaneh Yousefi Sharami; Fariba Farhadifar; Roya Tabatabaei (PAGEPress Publications, 2022)
The aim of this study was to investigate the recurrence rate and five-year survival in patients with borderline ovarian tumors and related factors. This retrospective cohort study was performed on 20 women diagnosed with a borderline ovarian tumor in Kurdistan province, Iran, between 2007 and 2019. Patients' records were reviewed and a researcher-made questionnaire was completed for each patient, which included demographic and clinical variables related to patient survival. The most common type of ovarian borderline tumor was the serous borderline ovarian tumor (75%). In fifty percent of the cases, cystectomy was used as th treatment. Recurrence was observed in three patients (15%), two of which were treated with cystectomy, and the other case was treated by TAH + BSO method (p = 0.64). There was no significant difference in terms of the type of surgery, history of infertility, history of taking contraceptive pills, age, age at diagnosis, and BMI between the two groups with and without recurrence (p > 0.05). The overall survival rate was 100% and none of the patients died at the end of follow-up. There was no relationship between any of the clinical and demographic variables with disease recurrence, and since all patients were alive after the end of the follow-up period. In summary, it was not possible to assess the relationship between patients' survival rate and studied variables.